Body composition of young people aged 17-18 years, practicing and not practicing swimming, with the use of the bioelectrical impedance method - Jendrysek, Marek; Nowosielska-Swadzba, Danuta; Zwolinska, Danuta; Podstawski, Robert (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: Body composition evaluation of youth aged 17-18 of a different physical activity with the help of bioelectric impedance method. Material and Methods: 18 boys practicing swimming and 19 boys not practicing it took part in the study, making up a control group. Height, weight, BMI, lean body mass, the content of fat and water, Rohr factor were evaluated. Non-parametric Mann-Whitney test has been used to evaluate the differences in the range of the tissue components between the two groups. Results: Statistically significant differences were found on the p<0,05 level in % fat content. Mean body weight in experimental group was 71.5 kg, while in control group it was 69.4 kg. Minimum and maximum weight in group of swimming-practicing persons was: 56.6-92.2 kg. Increased body weight in the group of swimmers can result from greater amount of active tissue in this group compared with persons of low physical activity. Proportionally, it amounted to 64.3 kg and 61.3 kg. In the tested groups, minimal and maximal values of amount of active tissue proportionately amounted to: 54.1-78 and 49.5-72,3 kg. Conclusions: Physical activity modifies body composition. Active lifestyle is one of the methods for prevention of overweight and obesity.